The Relationship of Time Management and Academic Procrastination: A Case of University Students - Ayşe Nihan Arıbaş (Selçuk Üniversitesi Sosyal Bilimler Enstitüsü Dergisi, 2021)
This research was conducted descriptively to determine the relationships between time management and academic procrastination. The sample of the study consists of 425 people. The data were analyzed using the snowball sampling method and Google survey; The Demographic Information Form was collected using the Time Management Scale and the Academic Delay Scale. Independent Sample T-Test, ANOVA Test, and Correlation Test were used to evaluate the data. 77.9% of the participants are women, and 91.8% are between the ages of 18-24. Time management total score average is 71.08 ± 12.69, and academic delaytotal score average is 62.71 ± 10.94. According to the correlation analysis results, a moderate negative correlation was found between time management and academic procrastination. As the academic delaylevels of students increase, their time management success decreases. The comparisons made determined that the variables of age, mother's approach, father's approach, voluntary coming to the department, family relationships, and friendship relations affect the time management scale scores. Besides, it was determined that the variables of gender, mother's approach, father's approach, age, and family relationships affect the academic delayscale scores. As a result, it was determined that demographic variables affect work-family conflict scores, life satisfaction, and job satisfaction scale.